Community empowerment through the utilization of coconut sap into bioethanol in Sabron Sari Village, Jayapura Regency - Hendry Y. Nanlohy; Helen Riupassa; Bonefasius Bao; Susi Marianingsih (Community Empowerment, 2023)
The negative impact that can arise with the increase in the population of Papua and limited land for jobs in rural areas, and the use of natural resources that have not been maximized is the occurrence of unemployment. The existence of abundant coconut plants in the Sabron Sari Village, Jayapura Regency, has vast natural potential. However, the reality is that it has not been appropriately utilized so far, especially as an energy source. This community service aims to utilize coconut sap into bioethanol as an alternative fuel to replace kerosene. The method used in this program is socialization and training on the benefits and potential of coconut plants as an alternative fuel source, the process of making bioethanol, and its use on stoves. The results obtained from this program show that the people of Sabron Sari village have a new perspective on the potential of coconut plants and can have excellent skills and abilities in producing household-scale bioethanol from coconut sap.